Тhe Russian statehood. 2017 - A. Butakov (Правоприменение, 2017)
The subject. The author's research methodology of social processes is represented, by establishinga bond between the ways of property organization and governmental form – especiallyits political regime.The analysis of methodology is based on the historical materials devoted to Russian statehoodin terms of its transition states during the appropriate industrialization of domesticproduction.The results, scope of application. Since 1861, the Russian statehood during its existence hasexperienced a number of important transitional states, where the successful process offorming the traditional foundations of the corresponding society in different periods (pre-Soviet, Soviet and post-Soviet) in terms of the author's methodology was and still is untenable.The basis of this methodology is the existing relationship between the concrete wayof property organization and its social function. Thus, a private way of property organizationreproduces the function of social development. A mixed (corporate) way provides a functionof social compromise (convergence). Finally, the common (collective) way of propertyorganization can be determined by the function of social security. A concrete way of propertyorganization arries out only a specific social function. An attempt to change this dependenceleads the corresponding society to the destruction of the foundations of its existence.Thus, the liquidation (abolition) of the private way of property organization objectivelyforms the impossibility of realizing the functions of social development and the functionsof social compromise (convergence) in the society by the common (collective) way ofits organization. There is another aspect of the relationship between a particular way oforganizing property and its social function. Each of the above methods of property organization,reaching a monopoly state that goes into rent, provides for self-destruction andtransformation of its social function as opposed to: from development to degradation, fromcompromise to confrontation, from social provision of society to the provision of clans. Abrief historical digression in the article makes it possible to disclose the content of thismethodology when analyzing the facts of life of Russian statehood, including its latest historyuntil 2017.Conclusions. The modern post-Soviet statehood in its various foundations: economic, political,social and cultural, when realizing the appropriate tendencies of segregation of theprivate way of property organization and the growing monopolization of state property,largely casts doubt on the future development of our society.